Identification of sequence polymorphisms in the mitochondrial cytochrome c oxidase genes as risk factors for hepatocellular carcinoma. Issue 3 (13th July 2017) - Wang, Hongfang; Xu, Jinsheng; Li, Demao; Zhang, Shenglei; Guo, Zhanjun
Abstract : Background: Single nucleotide polymorphisms (SNPs) accumulated in the mitochondrial DNA (mtDNA) is susceptible to the tumor formation. We discovered previously that SNPs in the mitochondrial displacement loop (D‐loop) was associated with the risk of hepatocellular carcinoma (HCC). Methods: The cytochrome c oxidase ( COX ) genes of mtDNA were sequenced between 107 HCC patients and 100 matched healthy controls. The χ 2 test was used to analyze single SNPs' statistical difference between HCC patients and healthy controls. Results: In this study, cancer risk‐associated SNPs in the COX genes of mtDNA coding region were assessed in HCC patients and health controls. The nucleotide position at site 9545A/G ( P=.036) was identified its association for HCC with the 9545G allele susceptible to cancer risk. Conclusions: The SNPs in the COX genes may help us to evaluate the cancer risk of HCC.